Methotrexate-conjugated zinc oxide nanoparticles exert a substantially improved cytotoxic effect on lung cancer cells by inducing apoptosis - Prakriti Mishra; Mohd Faizan Ali Ahmad; Lamya Ahmed Al-Keridis; Mohd Saeed; Nawaf Alshammari; Nadiyah M. Alabdallah; Nadiyah M. Alabdallah; Rohit Kumar Tiwari; Rohit Kumar Tiwari; Afza Ahmad; Mahima Verma; Shireen Fatima; et al. (Frontiers Media S.A., 2023)
In the current study, we report the synthesis of methotrexate-conjugated zinc oxide nanoparticles (MTX-ZnONPs) and their high efficacy against lung cancer cells. Conjugation of MTX with ZnONPs was authenticated by UV-vis spectroscopy, dynamic light scattering (DLS), Fourier-transform infrared (FTIR) spectroscopy, and transmission electron microscopy (TEM). This drug-nanoconjugate also showed high drug-loading efficiency. The therapeutic efficacy of MTX-ZnONPs was further tested in vitro against A549 cells, and the results of MTT and LDH release assays showed that MTX-ZnONPs, in addition to free MTX, were efficient in exerting cytotoxic effect on A549 cells; however, the effectiveness of MTX-ZnONPs was found to be considerably enhanced at very low doses compared to that of free MTX. Moreover, ZnONPs alone significantly inhibited the cell viability of A549 cells at a much higher concentration compared to MTX-ZnONPs and MTX. Furthermore, the cytomorphology of A549 cells was characterized by cellular shrinkage and detachment from the surface in all the treatment groups. Similarly, A549 cells, in all the treatment groups, showed fragmented and condensed nuclei, indicating the initiation of apoptosis. Mitochondrial membrane potential (ψm) in A549 cells showed a gradual loss in all the treatment groups. Results of the qualitative and quantitative analyses depicted increased reactive oxygen species (ROS) levels in A549 cells. The results of the caspase activity assay showed that MTX-ZnONPs andfree MTX caused significant activation of caspase-9, -8, and -3 in A549 cells; however, the effect of MTX-ZnONPs was more profound at very low doses compared to that of free MTX. Thus, our results showed high efficacy of MTX-ZnONPs, suggesting efficient intracellular delivery of the drug by ZnONPs as nanocarriers.